Дослідження процесу ущільнення відходів провіювання соняшнику з використанням змінних шнеків - Самойчук, Кирило Олегович; Самохвал, Віталій Анатолійович; Samoichuk, Kyrylo; Samokhval, Vitalii (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Проведено дослідження процесу ущільнення рослинної біомаси шнековим механізмом із метою виготовлення паливних брикетів. Виявлені закономірності стали підґрунтям для визначення оптимальних параметрів роботи обладнання. У процесі проєктування брикетувальних пресів необхідно враховувати особливості деформації біомаси, а також зміну її фізичних властивостей у момент контакту з робочими органами. Шнековий метод брикетування має перевагу завдяки поєднанню процесів транспортування й ущільнення, що забезпечує безперервність роботи за стабільної швидкості. Процес ущільнення біомаси шнековим механізмом відбувається у три стадії, та основним чинником, що впливає на продуктивність преса та якість брикету, є крок витків шнеків. Проведено експериментальні дослідження зі зміною кроків витків шнеків, що дали можливість визначити оптимальні показники пресового обладнання для отримання високої продуктивності та якісного щільного паливного брикету. /// EN: A study of the process of compaction of plant biomass with a screw mechanism for the production of fuel briquettes was conducted. The identified patterns became the basis for determining the optimal parameters of the equipment. In the process of designing briquetting presses, it is necessary to take into account the peculiarities of biomass deformation, as well as changes in its physical properties at the moment of contact with the working bodies. The screw briquetting method has the advantage of combining the processes of transportation and compaction, which ensures continuous operation at a stable speed. An important factor is the time spent by the briquetted material in the molding chamber at a constant temperature. At the initial stage of the compaction process, stresses are formed in the raw material, which cause complex, nonlinear deformations. These deformations are accompanied by displacement and reorientation of biomass particles without significant changes in their internal structure. At the second stage, as the load increases, a critical combination of stresses is reached, at which an equilibrium is established between the internal resistance forces of the material and the external forces applied by the working bodies of the equipment. This equilibrium is unstable and precedes a phase transition in the briquette structure. At the final third stage, a further increase in load causes the development of plastic deformations, as a result of which biomass particles change their shape and fit tightly together, which ensures final compaction and the formation of a strong briquette structure. The theoretical analysis of the process made it possible to establish the dependence of pressure on the length of the working body. It was found that the pressure increases in the direction from the feed hopper to the forming section. The disadvantage of most screw equipment is that its throughput capacity decreases with increasing briquette density.
Study of the process of compaction of sunflower hulling waste using a screw press extruder
Keywords: олія; достискання; дослідження; біомаса; брикет; прес; формування; oil; ripening; research; biomass; briquette; press; molding